An investigation of learning style preferences of nurses in training at two nursing schools in public health facilities in Cape Town - Fisher, Gohwa (Division of Nursing and Midwifery, 2016)
Aim: To investigate the preferred learning styles of learner nurses i.e. enrolled/staff nurses and auxiliary nurses, in nursing schools within public health facilities in the Cape Town Metropolitan district of the Western Cape, South Africa. Objectives: To determine individual learning styles of learner nurses registered for a training programme in a school of nursing. To establish the differences between the categories of learner nurses with regards to the learning style preference. To determine a possible relationship between demographic and educational background of the individual and the preferred learning style.